Rice Husk In Indonesia - Koentoro Soebijarso (Balai Besar Kimia dan Kemasan, 1978)
The paddy production in Indonesia should contain rice husk 20 - 25 %. bran 10 - 12 %, and rice 63 - 70 %. Rice husk usually burned to ash used as abrasive purposes for household application, and also rice husk used for burning bricks. In this case we are facing the secondary waste product which is rich in Si02 content, the ash from burning the rice husk as fuel.The characteristics for rice husk and ash (dry basis) from Tangerang & Karawang especially ash, Si02, CaO, MgO, and Fe2o3 are determinated.